Comprehensive analysis of the green-to-blue photoconversion of full-length Cyanobacteriochrome Tlr0924 - Hardman, Samantha J O; Hauck, Anna F E; Clark, Ian P; Heyes, Derren J; Scrutton, Nigel S (Biophysical journal, 2014)
Cyanobacteriochromes are members of the phytochrome superfamily of photoreceptors and are of central importance in biological light-activated signaling mechanisms. These photoreceptors are known to reversibly convert between two states in a photoinitiated process that involves a basic E/Z isomerization of the bilin chromophore and, in certain cases, the breakage of a thioether linkage to a conserved cysteine residue in the bulk protein structure. The exact details and timescales of the reactions involved in these photoconversions have not been conclusively shown. The cyanobacteriochrome Tlr0924 contains phycocyanobilin and phycoviolobilin chromophores, both of which photoconvert between two species: blue-absorbing and green-absorbing, and blue-absorbing and red-absorbing, respectively. Here, we followed the complete green-to-blue photoconversion process of the phycoviolobilin chromophore in the full-length form of Tlr0924 over timescales ranging from femtoseconds to seconds. Using a combination of time-resolved visible and mid-infrared transient absorption spectroscopy and cryotrapping techniques, we showed that after photoisomerization, which occurs with a lifetime of 3.6 ps, the phycoviolobilin twists or distorts slightly with a lifetime of 5.3 ?s. The final step, the formation of the thioether linkage with the protein, occurs with a lifetime of 23.6 ms.